Pandangan Ahmad Musthafa Al-Maraghi terhadap Ayat-Ayat Bala’ - Hasiah Hasiah; Sawaluddin Siregar (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Al- Qur'an is the word of Allah SWT. wich sometimes has words in it, which have many meanings like the word Bala’. The word reinforcements is implied in the Qur’an by commentators which has many meanings, Al-Maraghi who stated that Bala’ is a test and a trial. The formulation of the problem of this research is how systematic the interpretation of Bala’ verses according to Ahmad Musthafa Al-Maraghi, and how is the meaning of humans when Allah SWT. gives tests and trials. The goal is to avoid reinforcements by doing good deeds and staying away from the probibition of Allah SWT. and know the meaning of Bala’ to humans. This research is a library research that collects data sources in the from of primay and secondary library mateBala’’. And the concluded that Ahmad Musthafa Al-Maraghi said the word Bala’ in the Qur’an only gives the meaning of tests and trials as torment, punishment or calamity but can also be a warning to living creatures on this earth, not only for humans. Ahmad Musthafa Al-Maraghi uses the word Bala’ contained in the book of Tafsir Al-Maraghi to express the meaningof Bala’ which serves as a warning to humans so thatAllah SWT. sends down tests and trias to this servants in order to human patience when Allah SWT. bring Misfortune.